The toll-gate - Heyer, Georgette, frey50 (Naperville, Ill. : Sourcebooks Casablanca, 2011)
On his 38th birthday, lonely Scott Williams fervently wishes for a wife and family, but he never expects to become so utterly captivated by the beautiful, yet troubled Jennifer St. James.
Copyright date: 1954.
Keywords: England -- Social life and customs -- 19th century; Regency fiction; Love stories